PENGARUH CAPITAL ADEQUACY (CAR) TERHADAP PROFITABILITAS YANG DI UKUR DENGAN RETURN ON ASSET (ROA) PADA PT BANK DANAMON - Alffarizzi, Tauffik; Puji Muniarty (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
Abstract This study aims to analyze the effect of the capital ratio on profitability, as measured by Return on Assets (ROA), at PT Bank Danamon. The capital ratio is an important indicator in assessing a bank's health, particularly in facing the risk of loss. This study used quantitative methods with secondary data in the form of financial reports. The analysis technique used was simple linear regression. The results indicate that the capital ratio has a positive effect on ROA. This suggests that a higher capital ratio increases a bank's ability to generate profits.